WORKSHOP PENINGKATAN KUALITAS PEMBELAJARAN MATEMATIKA SD MELALUI MEDIA KOMIK PADA SDN 028 PEKKABATA - Asdar Asdar; Muhammad Assaibin; Ayu Rahayu (LP4MK STKIP PGRI Lubuklinggau, 2020)
This community service activity (PkM) aims to (1) increase the knowledge of SDN 028 Pekkabata teaching staff on the use of comic media as a learning medium and (2) increase the creativity of SDN 028 Pekkabata teachers in managing learning. This is achieved by conducting training on the use of comic media as a learning medium. The school that is a partner in implementing this PkM is SD Negeri 028 Pekkabata. This elementary school is one of the State Elementary Schools (SD) located in Polewali District, Polewali Mandar Regency, West Sulawesi Province. The methods used in this PkM are Forum Group Discussion (FGD) lectures, training and mentoring. The implementation stage of PkM includes (1) coordination and analysis of the needs of proposals, (2) compiling and validating the Comic Media module, (3) training on the creation and use of comic media, (4) mentoring in the classroom using commercial media, (5) evaluation and (6) ) reporting on the implementation of activities. Based on the results of the questionnaire data analysis prior to the implementation of the activity, it was found that 100% of SDN 028 Pekkabata teachers had never used comic media as a learning medium, and 99% had positive positive responses from the participants.